A STUDY OF LISTENING SKILLS THROUGH MOVIE: A REVIEW OF THE CURRENT LITERATURE - Yahfenel Evi Fussalam; Renda Lestari; Rensi Yu Anggelia (Journal Of Language Education and Development (JLed), 2019)
Listening skill is considered as a major factor of language learning and teaching since it is plays an important role in communication process. However, some media to improve student’s listening skill such as audio, visual, and audio-visual had been developed since past view decades, many students and the teachers do not pay enough attention to its importance media in their classes. In this article, the researchers review some important issues concerning the use of audio-visual media namely movie to provide a starting point for developing listening skill. It starts through a brief discussion of definition listening, analyzing some problems in listening comprehension, pursued by reviewing recommended film category and the structure of movie, tips to learn English through a movies, and discussion the relationships between watching movie and listening skills. The research result from the review of literature indicated that movie is the suitable media to help teacher explain the material thoroughly and concretely. Watching movie as media in teaching and learning process allows the students to understand the language in a form of natural contexts, since they can analyze the use of the language and make connections between words and images.